2011
DOI: 10.4049/jimmunol.1100620
|View full text |Cite
|
Sign up to set email alerts
|

Blocking IL-1 Signaling Rescues Cognition, Attenuates Tau Pathology, and Restores Neuronal β-Catenin Pathway Function in an Alzheimer’s Disease Model

Abstract: Inflammation is a key pathological hallmark of Alzheimer's disease (AD), though its impact on disease progression and neurodegeneration remains an area of active investigation. Among numerous inflammatory cytokines associated with AD, interleukin-1β (IL-1β) in particular has been implicated in playing a pathogenic role. Here we sought to investigate whether inhibition of IL-1β signaling provides disease-modifying benefits in an AD mouse model, and if so, by what molecular mechanisms. We report that chronic dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
256
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 377 publications
(294 citation statements)
references
References 81 publications
10
256
0
Order By: Relevance
“…We previously demonstrated that altered inflammation such as gliosis in the brain exacerbated tau pathology in 3xTg-AD mice (Kitazawa et al, 2005(Kitazawa et al, , 2011. Accordingly we investigated pathological changes in tau after upregulation of GLT-1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that altered inflammation such as gliosis in the brain exacerbated tau pathology in 3xTg-AD mice (Kitazawa et al, 2005(Kitazawa et al, , 2011. Accordingly we investigated pathological changes in tau after upregulation of GLT-1.…”
Section: Resultsmentioning
confidence: 99%
“…As described previously (Kitazawa et al, 2011), the apparatus used for the MWM task was a circular aluminum tank (1.2-m diameter) painted white and filled with water maintained at 22e24 C. The maze was located in a room containing several simple visual extramaze cues. Mice were trained to swim and find a 14-cm diameter circular clear Plexiglas platform submerged 1.5 cm beneath the surface of the water and invisible to the mice while swimming.…”
Section: Cognitive Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of IL-1 signaling signiicantly suppressed the activation of cdk5/p25, GSK-3β, and p38-MAPK, all major kinases that phosphorylate tau in neurons. Another study demonstrated a direct efect of IL-1β secreted by microglia on neurons and subsequent activation of p38-MAPK and accumulation of tau phosphorylation [69]. NSAIDs could be repurposed as NLRP3 inlammasome inhibitors that provide neuroprotective impact against AD [70].…”
Section: Interleukin 1 Receptormentioning
confidence: 99%
“…IL-1β has been reported to increase the expression of APP in neuronal culture [69]. The amyloid precursor protein (APP), via stimulation of amyloidogenic processing, undergoes sequential proteolytic cleavage by β-secretase and γ-secretase to generate Aβ.…”
Section: Il-1r Signaling In Neuronsmentioning
confidence: 99%